Spectrum of Alcoholic Liver Disease in Tribal Alcoholics of Chittagong Hill Tracts of Bangladesh - Biswas, Sarmistha; Paul, Sujat; Syeed, Abu; Mahbub, Md Shahriar; Khan, Mohammad Ashik Imran; Gupta, Ratan Das; Miah, Md Titu; Ayaz, KFM; Das, Aparna; Alam, Md Billal; et al. (Journal of Medicine, 2011)
Background: Alcohol is one of the most important causes of liver disease. In Bangladesh, alcoholism is not a usual practice among the general population as there are social and religious barriers against it. But in the Hill tracts, there is no social stigma in taking alcohol. Relatively little is known about this aspect in Bangladesh. This small-scale study was done to identify the spectrum of liver disease among tribal people. Material and Methods: A descriptive, observational clinical study was conducted for a period of six months (1st July, 2007 to 31st December, 2007) on a series of 50 tribal alcoholic people, collected from General Hospital and the tribal community of Rangamati Hill District. Subjects were included from both the urban and rural area of different socioeconomic classes. History, meticulous clinical examination and investigations were done to detect the pattern of alcohol induced liver injury. Results: Among the 50 cases, 47 patients were male and 3 were female cases. Both regular and irregular drinkers were included. The common symptoms of liver disease among tribal alcoholics were yellow coloration of sclera (24%), nausea & vomiting (20%) and weight loss (14%). The common findings were jaundice (24%), anemia (20%), ascites (10%), edema (10%) and hepatosplenomegaly (20%). Liver function tests revealed only 17 patients had mild to severe form of hepatocellular damage. Hyperbilirubinemia was found in 34% participants. AST/ALT ratio more than 2 was found in 32% subjects. Ultrasonography was done in 46 out of 50 subjects: 29 cases reported as normal (63.04%), fatty liver in 5 (10.87%), acute hepatitis in 5 (10.87%) and chronic liver disease in 7 (15.22%) cases. Liver biopsy was possible in 4 suspected cases (clinically and biochemically) of alcoholic liver cirrhosis and histology supported the clinical diagnosis in these cases. So, alcohol induced liver damage was noticed only in 17 cases. Nearly two-thirds of the participants were free from any form of liver disease. Conclusion: Despite the presence of risk factors for developing alcoholic liver disease, the prevalence was found to be low among the tribal alcoholic participants in this study. Keyword: Alcoholic liver disease; alcoholic fatty liver; alcoholic hepatitis; alcoholic liver cirrhosis; tribal population; Bangladesh DOI: 10.3329/jom.v12i1.6925 J Medicine 2011; 12 : 7-11